2017
DOI: 10.1002/sctm.17-0065
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cell-Derived Oligodendrocyte Progenitor Cells: Preclinical Efficacy and Safety in Cervical Spinal Cord Injury

Abstract: Cervical spinal cord injury (SCI) remains an important research focus for regenerative medicine given the potential for severe functional deficits and the current lack of treatment options to augment neurological recovery. We recently reported the preclinical safety data of a human embryonic cell-derived oligodendrocyte progenitor cell (OPC) therapy that supported initiation of a phase I clinical trial for patients with sensorimotor complete thoracic SCI. To support the clinical use of this OPC therapy for cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 46 publications
(83 reference statements)
2
74
0
Order By: Relevance
“…A critical feature of the derived cells is the myelination capacity that can be assessed either in vitro using oligodendroglial‐neuronal co‐cultures or nanofibers mimicking axons (Pedraza et al, ; Stacpoole et al, ; Sundberg et al, ; Wang et al, ) or in vivo by transplantation experiments (Izrael et al, ). Additionally, a wealth of studies exploited in vivo myelination assays to demonstrate the use of ESC derived OPC as a cell‐based therapeutic strategy after irradiation therapy (Piao et al, ) or spinal cord injury (Keirstead et al, ; Kim et al, ; Manley, Priest, Denham, Wirth 3rd, & Lebkowski, ; Nistor et al, ; Sharp, Frame, Siegenthaler, Nistor, & Keirstead, ).…”
Section: Generation Of Oligodendrocytes From Pluripotent Cellsmentioning
confidence: 99%
“…A critical feature of the derived cells is the myelination capacity that can be assessed either in vitro using oligodendroglial‐neuronal co‐cultures or nanofibers mimicking axons (Pedraza et al, ; Stacpoole et al, ; Sundberg et al, ; Wang et al, ) or in vivo by transplantation experiments (Izrael et al, ). Additionally, a wealth of studies exploited in vivo myelination assays to demonstrate the use of ESC derived OPC as a cell‐based therapeutic strategy after irradiation therapy (Piao et al, ) or spinal cord injury (Keirstead et al, ; Kim et al, ; Manley, Priest, Denham, Wirth 3rd, & Lebkowski, ; Nistor et al, ; Sharp, Frame, Siegenthaler, Nistor, & Keirstead, ).…”
Section: Generation Of Oligodendrocytes From Pluripotent Cellsmentioning
confidence: 99%
“…Over the past two decades, many studies have evaluated the therapeutic potential of transplanting human NS/PCs or oligodendrocyte progenitor cells (OPCs), the intermediary progenitors between NS/PCs and mature oligodendrocytes (Fig. ), to regenerate CNS tissues after injury . While NS/PCs can become neurons, astrocyte or oligodendrocytes, OPCs are restricted to the oligodendrocyte lineage.…”
Section: Introductionmentioning
confidence: 99%
“…While NS/PCs can become neurons, astrocyte or oligodendrocytes, OPCs are restricted to the oligodendrocyte lineage. Differentiation of transplanted NS/PCs toward oligodendrocytes has led to significant gains in functional recovery in rodent models of spinal cord injury . Furthermore, transplantation of OPCs has shown some promise for spinal cord injury repair in recent clinical trials .…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell‐based therapy, especially BMSCs, has yielded encouraging results . BMSCs transplantation therapy is promising in mitigating the extent of SCI, not only due to a favorable ethical profile and safety, but also due to providing beneficial effects on various postinjury aspects: inflammation, apoptosis, axonal regrowth, angiogenesis, tissue sparing, astroglial scar, and motor recovery .…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell-based therapy, especially BMSCs, has yielded encouraging results. [5][6][7][8] BMSCs transplantation therapy is promising in mitigating the extent of SCI, not only due to a favorable ethical profile and safety, but also due to providing beneficial effects on various postinjury aspects: inflammation, apoptosis, axonal regrowth, angiogenesis, tissue sparing, astroglial scar, and motor recovery. [9][10][11][12] It is well known that BMSCs secrete a large variety of molecules and many studies have shown beneficial impacts from these factors such as brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF), epidermal growth factor (EGF), and more.…”
Section: Introductionmentioning
confidence: 99%